Medication and nutritional supplement use before and after bariatric surgery - Backes, Charline Fernanda; Lopes, Edyane; Tetelbom, Airton; Heineck, Isabela (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Bariatric surgery has been an effective alternative treatment for morbid obesity and has resulted in decreased mortality, better control over comorbidities and reduced use of drugs. The objective of this study was to analyze the impact of bariatric surgery on medication drug and nutritional supplement use. DESIGN AND SETTING: Longitudinal study of before-and-after type, on 69 morbidly obese patients in a public hospital in Porto Alegre. METHODS: Through interviews, the presence of comorbidities and use of drugs with and without prescription were evaluated. RESULTS: Among the 69 patients interviewed, 85.5% had comorbidities in the preoperative period, with an average of 2.3 (± 1.5) per patient. The main comorbidities reported were hypertension, diabetes and dyslipidemia. 84.1% of the patients were using prescribed drugs in the preoperative period. The mean drug use per patient was 4.8, which decreased to 4.4 after the procedure. The surgery enabled significant reduction in use of most antidiabetic (84%), antilipemic (77%) and antihypertensive drugs (49.5%). On the other hand, there was a significant increase in use of multivitamins and drugs for disorders of the gastrointestinal tract. The dosages of most of the drugs that continued to be prescribed after surgery were decreased, but not significantly. CONCLUSION: After bariatric surgery, there were increases in the use of vitamins, gastric antisecretory drugs and antianemic drugs. Nevertheless, there was an overall reduction in drug use during this period, caused by suspension of drugs or dose reduction.